#TITLE_ALTERNATIVE# - SUMANTRI NIM : 20714317, SURYA
Glibenclamide is a class of sulfonylureas used orally as a type 2 antidiabetic drug, categorized as a class II BCS drug because it has low solubility and bioavailability. One way to increase the dissolution rate is made in the form of nanoparticles, with Nanostructured Lipid Carrier as a delivery system. The purpose of this research is to develop Glibenclamide NLC delivery system. Formulated by screening for the selection of solid lipids (glyceryl monosterate, cetyl alcohol, stearyl alcohol and stearic acid) liquid lipids (oleic acid, virgin coconut oil, isopropyl myristate, and olive oil), varying the combination of solid lipids and liquid lipids as well as surfactants. The Glibenclamide NLC was prepared by high-speed homogenization and ultrasonication method, to an optimized Glibenclamide NLC formula, consisting of 2% glyceryl monostearate as solid lipid, 2% oleic acid as liquid lipid, 4% Polysorbate 80 as surfactant. Characterization is the measurement of particle diameter and polydispersity index, Efficiency Entrapment, Differential Scanning Microscopy, FTIR, test in simulation of gastrointestinal condition, morphological characterization with Transmission electron microscopy (TEM). NLC-GL has a particle size of 140.30 ± 1.03 nm, polydispersity index of 0.289 ± 0.068, an adsorption efficiency of 73.63 ± 0.33%. From this study it is concluded that NLC-GL has the potential to increase the solubility of the active substance, and by itself increases the bioavailability of the drug.